Influence of pulse operational parameters on pure nickel electrodeposits: Part II. Microhardness and corrosion resistance. (1st February 2017) - Sajjadnejad, M.; Omidvar, H.; Javanbakht, M.
Abstract : Nanocrystalline nickel electrodeposits were fabricated from an additive-free Watts bath by pulse current electrodeposition technique. The coatings were obtained at different current densities, duty cycles and pulse frequencies and were characterised using Field Emission Scanning Electron Microscope and X-ray diffraction. The corrosion properties of the coatings in 3.5 wt-% NaCl solution were investigated using potentiodynamic polarisation and electrochemical impedance spectroscopy. All the nickel samples exhibited active–passive potentiodynamic polarisation behaviour. A strong relationship was observed between the crystallographic orientation of the nickel electrodeposits and their corrosion resistance. Commonly the corrosion current density increases with I( 200) / I (111) ratio ( I (hkl) is the peak intensity corresponding to (hkl) crystal plane). The passive layer is more stable on [211] oriented grains than on [100] oriented grains. The Nyquist impedance curves were composed of two depressed semicircles corresponding to charge transfer process and diffusion process through a porous passive layer. [211] orientation and small grain size favour high microhardness values.